Incorporation of Plasmid DNA Into Bacterial Membrane Vesicles by Peptidoglycan Defects in Escherichia coli - Aktar, Sharmin; Okamoto, Yuhi; Ueno, So; Tahara, Yuhei O.; Imaizumi, Masayoshi; Shintani, Masaki; Miyata, Makoto; Futamata, Hiroyuki; Nojiri, Hideaki; Tashiro, Yosuke (Frontiers in Microbiology, 2021)
Membrane vesicles (MVs) are released by various prokaryotes and play a role in the delivery of various cell-cell interaction factors. Recent studies have determined that these vesicles are capable of functioning as mediators of horizontal gene transfer. Outer membrane vesicles (OMVs) are a type of MV that is released by Gram-negative bacteria and primarily composed of outer membrane and periplasm components; however, it remains largely unknown why DNA is contained within OMVs. Our study aimed to understand the mechanism by which DNA that is localized in the cytoplasm is incorporated into OMVs in Gram-negative bacteria. We compared DNA associated with OMVs using Escherichia coli BW25113 cells harboring the non-conjugative, non-mobilized, and high-copy plasmid pUC19 and its hypervesiculating mutants that included ΔnlpI, ΔrseA and ΔtolA. Plasmid copy per vesicle was increased in OMVs derived from ΔnlpI, in which peptidoglycan (PG) breakdown and synthesis are altered. When supplemented with 1% glycine to inhibit PG synthesis, both OMV formation and plasmid copy per vesicle were increased in the wild type. The bacterial membrane condition test indicated that membrane permeability was increased in the presence of glycine at the exponential phase, in which cell lysis did not occur. Additionally, quick-freeze deep-etch and replica electron microscopy observations revealed that outer-inner membrane vesicles (O-IMVs) are formed in the presence of glycine. Thus, two proposed routes for DNA incorporation into OMVs under PG-damaged conditions are suggested. These routes include DNA leakage due to increased membrane permeation and O-IMV formation. Additionally, our findings contribute to a greater understanding of the vesicle-mediated horizontal gene transfer that occurs in nature and the utilization of MVs for DNA cargo.